Cardiovascular disease in women with early-onset preeclampsia: a matched case-control study - Domínguez del Olmo, P.; Herraiz, I.; Villalaín, C.; De la Parte, B.; Rodríguez-Sánchez, E.; Ruiz-Hurtado, G.; Fernández-Friera, L.; Morales, E.; Ayala, J. L.; Solís, J.; Galindo, A. (The journal of maternal-fetal & neonatal medicine, 2025)
To compare the risk of cardiovascular disease and the occurrence of cardiovascular events in the mid-long term after delivery, between women with and without a history of early-onset preeclampsia. A prospective case-control study has been conducted in Hospital Universitario 12 de Octubre, Madrid. 50 women with early-onset preeclampsia (diagnosed < 34 + 0 weeks) who delivered between 2008 and 2017 and a matched group (by age, parity, pregestational body mass index and date of delivery) of 50 women with uncomplicated pregnancies were recruited. In them, a 1-day visit for cardiovascular assessment was performed 3-12 years after delivery, consisting of the completion of blood and urine tests including oxidative stress analysis, vascular ultrasound to assess subclinical atherosclerosis and 24-hour blood pressure monitoring. Furthermore, Framingham10 and Framingham30 scales of cardiovascular disease risk were applied. Univariate analysis was used for comparisons, and the Kaplan-Meier method was performed to estimate their survival time until the development of a cardiovascular disease event (chronic hypertension, renal disease, myocardial infarction, thromboembolism and cerebrovascular disease). Patients were evaluated at a median of 7.5 years (interquartile range, 6.5-9) after delivery. Women with a history of early-onset preeclampsia vs controls showed significantly lower levels of hemoglobin (12.9 vs 13.7 g/dL), hematocrit (38.9 vs 40.8%), prothrombin activity (93.1 vs 99.8%), IgA (223.5 vs 279.9 mg/dL) and C3 factor (101.0 vs 110.5 mg/dL) and prolongated prothrombin time (12.4 vs 11.6 s). Early-onset preeclampsia cases showed worse blood pressure control, with higher percentages of over-limit systolic blood pressure (17.9 vs. 11.2%, < 0.01) and diastolic blood pressure (28.1 vs. 18.7%, < 0.01) readings in 24 h. There were no significant differences in the vascular ultrasound studies as well as in the estimated cardiovascular risk obtained with the Framingham scales. At the visit time, a cardiovascular event was present in 44% women with history of early-onset preeclampsia vs 10% in the control group ( < 0.01). The most common event was chronic hypertension, with a relative risk of 4.7 (95% confidence interval 1.7-13.0) for the early-onset preeclampsia group. Women with a history of early-onset preeclampsia, compared to their matched controls, showed a greater risk of cardiovascular disease mainly at the expense of a 4.7-fold risk of developing chronic hypertension, with a median follow-up of 7.5 years after delivery.